An Examination Into the Communicative Functions of Code-Switching and Code-Mixing in the Teaching and Learning Process - Gede Eka Wahyu (Journal of Innovative and Creativity, 2025)
This study aims to explores the phenomena of code switching and code mixing within instructional settings, focusing on lecturers and instructors engaged in the teaching and learning process. Employing a qualitative approach with a descriptive qualitative design, the research aims to describe and analyze the types and functions of language alternation used by educators. Data were analyzed using the interactive model proposed by Miles and Huberman, encompassing data reduction, data display, and conclusion drawing/verification. The respondents consisted of lecturers and vocational instructors observed during classroom and practical teaching activities. The findings reveal that both lecturers and instructors employed various forms of code switching and code mixing, including inter-sentential switching, intra-sentential switching, tag switching, and insertion. These language practices were utilized to enhance comprehension, clarify concepts, and adapt to the students’ linguistic competencies, thereby facilitating more effective communication in educational contexts.